Kajian KAJIAN DOGMATIKA TENTANG IDENTITAS KRISTUS BAGI KAWULA MUDA KRISTEN - Mey Daman Lawolo (Jurnal Missio Cristo, 2023)
This article shows that Christ, who is the center of Christianity, is often misunderstood by Christians. In particular, young people who are the next generation of the church have a less comprehensive knowledge of Christ due to the church's role in paying less attention to doctrinal teaching in the congregation. For young people, Christ is known only as a helper, family, and when identifying Christ with the Father and the Holy Spirit. Therefore, in this article, the author aims to rectify this misunderstanding and equip young people through church services to recognize Christ as a divine and human Person who has a distinction with the Father and the Holy Spirit. Through the literature review research method, the author presents the identity of Christ that must be understood by young people as the central existence of Christian beliefs on which Christian beliefs rest. By investigating biblical revelations and related literature, the author concludes that Jesus Christ is not only a person who is willing to help and become the head of the Christian family. In fact, Christ is not the Father or the Holy Spirit. Christ is a person who is different from the Father and the Holy Spirit. He is God who became man (John 1:14) in order to save sinful humanity. Therefore, the Person of Christ is the Savior of mankind who must be known and preached by the youth from an early age. ABSTRAK BAHASA INDONESIA Artikel ini menunjukkan bahwa Kristus menjadi pusat Kekristenan sering disalahpahami oleh orang Kristen. Khususnya kawula muda yang menjadi generasi penerus gereja memiliki pengenalan yang kurang komprehensif terhadap Kristus dikarenakan peran gereja yang kurang memerhatikan pengajaran doktrinal di kalangan jemaat. Bagi kawula muda, Kristus dikenal sebatas Penolong, Keluarga, dan tatkala mengidentikkan Kristus dengan Bapa dan Roh Kudus. Oleh karena itu, dalam artikel ini Penulis bertujuan untuk meluruskan pemahaman yang keliru tersebut serta memperlengkapi kawula muda melalui pelayanan gereja supaya mengenal Kristus sebagai Pribadi ilahi dan manusia yang memiliki distingsi dengan Bapa dan Roh Kudus. Melalui metode penelitian kajian pustaka, Penulis  menyajikan identitas Kristus yang harus dipahami oleh kawula muda sebagai sentral eksistensi kepercayaan umat kristiani yang padanya bersandar kepercayaan orang Kristen. Dengan menyelidiki penyataan Alkitab dan literatur-literatur yang terkait, Penulis menyimpulkan bahwa Yesus Kristus tidak hanya sebatas Pribadi yang bersedia menolong dan menjadi Kepala Keluarga umat Kristen. Bahkan Kristus bukanlah Bapa atau Roh Kudus. Kristus adalah Pribadi yang berbeda dengan Bapa dan Roh Kudus. Dia adalah Allah yang menjadi manusia (Yoh. 1:14) demi menyelamatkan umat manusia yang berdosa. Oleh sebab itu, Pribadi Kristus adalah Juruselamat manusia yang harus dikenal dan diberitakan oleh kawula muda sejak dini.